MULTIDIMENSIONAL LOGARITHMIC SPHERICAL ΜU-LAW QUANTIZATION (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
Several researchers considered logarithmic spherical signal quantization. The design of a logarithmic spherical quantizer in k dimensions is considered in this paper. Logarithmic quantization is here used for vectors consisting of samples in sphere coordinates. The combination of logarithmic and spherical quantization (LSQ) is an efficient multi-dimensional quantization method at a high dynamic range, by preserving the original signal as close as possible.  The signal-to-noise ratio (SNR) and its dependence on the sphere dimension at lower bit rates are derived and discussed in this paper.
Keywords: Logarithmic spherical quantization